Peran Panglima Laot Dalam Adaptasi Sosial Nelayan Tangkap Ikan di Gampong Ujong Drien - Cut Eka Mutia; Herin Santiara; Miftahul Khoiriyah; Fazillah Baihaqi; Ahlun Nazar; Sopar (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Gampong ujong drien is a village located in Meureubo District, West Aceh Regency, Aceh Province, Indonesia. One of the activities carried out in Gampong Ujong Drien is community service aimed at empowering the potential of residents through the use of technology, especially the Village Information System (SIGAP). Panglima Laot is a fisherman leader who plays an important role in coordinating fisherman activities, resolving, and enforcing customary law. Panglima Laot also plays a role in regulating fishing and imposing sanctions on violators of customary law. This study will likely examine the conditions in Panglima Laot, their role in managing marine resources, and the factors that influence fishermen's perceptions of this role.